(untitled) (Journal of Educational Sciences, 2026)
In the context of the rapid digitalization of education, one of the priority areas in the training of future geography teachers is to improve their digital literacy. Currently, these works cannot be carried out without the use of artificial intelligence (AI) technologies. The purpose of the study is to identify the possibilities and specifics of developing the digital literacy of future geography teachers using artificial intelligence and to suggest ways to introduce them into geographical education. To achieve this goal, a literature review and comparative analysis of scientific works within the framework of the topic were used. Advanced educational methods based on artificial intelligence were studied, including personalized learning platforms, geographic information systems and virtual models. The advantages of introducing AI into the educational environment are scientifically proven. In addition, potential difficulties are identified, scientifically based conclusions are made and recommendations are made for the effective introduction of AI into the process of training future geography teachers. The scientific value lies in the proposal of a new model for the use of artificial intelligence technologies in the context of digitalization of geography education. The practical significance lies in the fact that the study enables the systematic development of digital literacy in future teachers by integrating the obtained results into pedagogical disciplines at higher education institutions, including the content of the courses “Methodology of Teaching Geography” and “Digital Technologies in Education.” Keywords: digital competence, artificial intelligence, geographical education, pedagogical technologies, innovative approaches